Comparison of Post-operative Pain and Hemorrhage in Different Techniques of Tonsillectomy - Safi, Md Abdullahis; Islam, Md Tarikul; Mazumder, Md Anayet Karim (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: Tonsillectomy is a surgery to remove the tonsils. It's one of the most common surgeries both teens and kids get. The merits and demerits of different surgical techniques for tonsillectomy is an ongoing debate. Through ages different techniques have been tried to improve the post- surgical outcome and reduce morbidity among patients. Objective: To compare the post-operative pain and hemorrhage among the patients underwent tonsillectomy by cold dissection and bipolar electrocautery method. Methods: Ninety patients who went through tonsillectomy in ENT departments of CMH Rangpur during last 2 years were included in this study. Patients were randomly distributed to undergo above were informed about two techniques of tonsillectomy. The statistics of post-operative pain and hemorrhage were examined and result were analyzed. Results: The immediate post-operative pain following tonsillectomy was found higher among the group went through tonsillectomy by bipolar electrocautery method than that of the cold dissection method, where extent of pain was measured by VAS score. On the contrary, Complications of post-operative hemorrhage were seen in 3.33% patients following tonsillectomy by cold dissection method and 1.11% patients were facing this type of complications following tonsillectomy by bipolar electrocautery dissection method. Conclusion: Statistically significant pain were found post- operatively following tonsillectomy in case of bipolar cautery dissection and complication of hemorrhage following tonsillectomy was more seen in cold dissection technique. JAFMC Bangladesh, Vol 21, No 1 (June) 2025:24-27